Two new species of Ascomycota on bamboo leaves in Fujian, China - Guan, Xiayu; Zhao, Zhiying; Keyhani, Nemat O.; Mu, Taichang; Zheng, Minhai; Yang, Lixia; Mao, Yuchen; Shang, Junya; Yang, Jiao; Pu, Huili; Lin, Yongsheng; Zhu, Mengjia; et al. (Frontiers in Microbiology, 2025)
IntroductionBamboo is the largest member of the family Poaceae, and these fast-growing plants have many beneficial ecological effects. Both mutualistic and pathogenic fungi associate with bamboo, however, only a limited number of such fungal species have been identified, and information concerning the diversity of fungi that parasitizes bamboo leaves is sparse.MethodsFungi were isolated from diseased leaves of bamboo from Fujian Province, China. Nucleotide sequences of four genetic loci were used for taxonomic and phylogenetic reconstruction. In addition, the morphological characteristics of fungal structures as well as growth parameters were characterized.ResultsWe report two new fungal species, one each within the Didymosphaeriaceae and Magnaporthaceae, both diverse genera that include saprophytes, endophytes, and pathogens. Based on combined morphological and phylogenetic analyses, including the nucleotide sequences of the internal transcribed spacer (ITS), the 28S large subunit of ribosomal RNA (LSU), the 18S small subunit of nuclear ribosomal RNA gene (SSU), the large subunit of RNA polymerase I (rpb1), and the translation elongation factor 1-α gene (tef1-α), the two new species described herein have been named as Bifusisporella magnum sp. nov., and Letendraea bambusae sp. nov. Detailed descriptions and morphological features of the species are provided.DiscussionThese data identify and describe new species within the Didymosphaeriaceae and Magnaporthaceae, expanding the diversity and distribution of fungi associating with bamboo.